Estimation of coating thickness of polymer coated NR gloves - Eng A H (Journal of Rubber Research, 2002)
The coating thickness of polymer coated NR gloves was estimated by using a stylus surface profile machine. During the measurement, the gloves were stretched to a suitable length, and the polymer layer which was harder than NR, cracked exposing the NR to the surface. When the stylus was driven across the surface, the sharp-pointed end of the stylus dropped into, and came out from the cracks, generating a series of peaks that corresponded to the coating thickness of the polymer layer. The coating thickness of the polymer-coated gloves in cuff, palm, and finger regions was measured and compared. The significance of the results is discussed in relation to the way these gloves were made.
Keywords: Coating; Gloves; NR; Polymer; Surface profile; Thickness